Navigating the divided city: Place identity and the time-geography of segregation. (December 2022) - Dixon, John; Sturgeon, Brendan; Huck, Jonny; Hocking, Bree; Jarman, Neil; Bryan, Dominic; Whyatt, Duncan; Davies, Gemma; Tredoux, Colin
Abstract: Research on segregation has expanded beyond its traditional focus on the residential demography of cities to explore how, why and with what consequences segregation manifests within activity spaces outside the home. As part of this shift, researchers have become increasingly interested in the time geography of residents' everyday mobility practices. Building on this work, the present paper explores the role of place identity dynamics in shaping how Catholic and Protestant residents navigate everyday spaces over time in the historically divided city of Belfast. To do so, we employ a novel combination of walking interviews (n = 33), GPS tracking, GIS visualizations, and photo-elicitation. By recovering residents' lived experiences of moving through the sensuous, material, and symbolic landscapes of the city, we show how the interrelated dynamics of place belonging and alienation influence their mobility choices in ways that maintain sectarian divisions. We also show how the concept of place identity enriches the materialist notion of mobility 'constraints' that has characterized most time geographic work on segregation. In conclusion, we suggest that interventions to promote desegregation must transform not only relations between different communities, but also relations between community members and the activity spaces in which their everyday movements are embedded. Highlights: Segregation is maintained through everyday mobility practices in divided cities. Such practices are shaped by residents' sense of place identity. Mobile methods such as GPS tracking and walking interviews can provide new data on place identity dynamics. Interventions to promote desegregation must transform the activity spaces in which residents' everyday movements are embedded.